2014
DOI: 10.1111/ajpy.12037
|View full text |Cite
|
Sign up to set email alerts
|

University Student Depression Inventory: Measurement model and psychometric properties

Abstract: University Student Depression Inventory (USDI) was developed to assess the symptoms of depression among the university students. Considering the debilitating nature of depression among university students globally, USDI was translated in Persian and validated using university students from Iran. A battery including the Persian version of USDI and scales measuring suicide, depression, and stress was administered to a normative sample of 359 undergraduate students, and an additional clinical sample of 150 studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…This 30‐item scale measures depression symptoms that may be more specific to students versus general clinical depression inventories. The USDI has been reported to have strong reliability and validity (Habibi et al., 2014; Khawaja & Bryden, 2006; Romaniuk & Khawaja, 2013) and convergent validity with previously validated measures of depression, including the BDI‐2 (Habibi et al., 2014) and the depression subscale of the Depression Anxiety Stress Scale (DASS; Khawaja & Bryden, 2006). Each item on the USDI is scored using a 5‐point Likert scale ranging from 1 ( not at all ) to 5 ( all the time ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This 30‐item scale measures depression symptoms that may be more specific to students versus general clinical depression inventories. The USDI has been reported to have strong reliability and validity (Habibi et al., 2014; Khawaja & Bryden, 2006; Romaniuk & Khawaja, 2013) and convergent validity with previously validated measures of depression, including the BDI‐2 (Habibi et al., 2014) and the depression subscale of the Depression Anxiety Stress Scale (DASS; Khawaja & Bryden, 2006). Each item on the USDI is scored using a 5‐point Likert scale ranging from 1 ( not at all ) to 5 ( all the time ).…”
Section: Methodsmentioning
confidence: 99%
“…No participants met exclusion criteria relating to the USDI. The researcher recorded each participant's total score and subscale scores (Habibi et al., 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The validity and reliability of the USDI have already been investigated by several researchers. Psychometric validation studies using multi-cultural student populations confirmed the factor structure of the USDI (Sharif et al 2011;Romaniuk and Khawaja 2013;Khawaja et al 2013;Habibi et al 2014). To obtain a measure of student depression using the USDI, the ordinal scores for all the items are summated, and a higher total indicates a higher risk of depressive disorder.…”
Section: Introductionmentioning
confidence: 92%
“…Τόσο η ιρανική εκδοχή του USDI που χορηγήθηκε σε 509 φοιτητές στο Ιράν, όσο και η πορτογαλική εκδοχή που χορηγήθηκε σε 321 φοιτητές πανεπιστημίων της Πορτογαλίας, παρουσιάζουν ικανοποιητικούς δείκτες εσωτερικής συνοχής και επαναληπτικών μετρήσεων, αλλά και υψηλή συγχρονική, συγκλίνουσα και αποκλίνουσα εγκυρότητα, γεγονός που τα καθιστά αξιόπιστα και έγκυρα εργαλεία, κατάλληλα για χρήση στο φοιτητικό πληθυσμό. Όπως προέκυψε μετά από τη διερευνητική και την επιβεβαιωτική ανάλυση παραγόντων, η πορτογαλική εκδοχή του USDI, επιβεβαίωσε την παραγοντική δομή του αρχικού εργαλείου (Santos, Pereira, & Veiga, 2008), ενώ στην ιρανική εκδοχή, το μοντέλο το οποίο προτείνεται είναι εκείνο των τριών πρώτης-τάξης παραγόντων και του ενός δεύτερης-τάξης γενικού παράγοντα (Habibi, Khawaja, Moradi, Dehghani, & Fadaei, 2014).…”
Section: η κλίμακα University Student Depression Inventory (Usdi)unclassified